“WHAT’S UP WITH THE INSTRUCTOR'S QUESTIONS IN WHATSAPP?” STUDENTS’ VOICES - Sugianto, Ahmad; Andriyani, Devi (IKIP Siliwangi, 2021)
The way an instructor utilizes questions constitutes an essential issue to ponder. By understanding them, the interaction between the instructor and students and the students’ performance of certain tasks can be construed. However, it may be challenging when it comes up to online learning for the situation is different from the situation they commonly experience via a face to face learning. Thus, this study aimed to reveal the questions deployed by the instructor, and the students perceived it during the online learning over six sessions using a WhatsApp group. It was conducted in one university in Bandung city. Twenty-three graduate students and an instructor were involved. A mixed-method with an embedded design was utilized and the data were garnered through online archives and interviews. Through the online archives, the types of questions used were investigated. Meanwhile, some systematic coding procedures were employed to analyze the students' voices of the questions used. The findings revealed that convergent questions were the most frequent type of questions found followed by divergent questions, procedural questions, and rhetorical questions consecutively. Besides, most of the students perceive positive views related to the questions used. However, some challenges still emerged during the online class.